2015
DOI: 10.1007/s10067-015-3077-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of colchicine and disease severity on physical growth in children with familial Mediterranean fever

Abstract: This study aimed to investigate the effects of colchicine on growth parameters in familial Mediterranean fever (FMF) patients. Fifty-one (29 girls, 22 boys) FMF patients were enrolled in the study. All of the patients were in the prepubertal stage and had not received colchicine treatment before the study. Anthropometric measurements, demographic features, clinical findings at diagnosis and during periods of attacks of FMF, disease activity, frequency of exacerbations, colchicine dosage, and weight and height … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…8 Two recent studies also showed that disease severity was not correlated with growth parameters; however, these data were obtained from small numbers of patients. 9,10 Disease severity assessment may be helpful in daily practice in terms of predicting the prognosis and guidance of patients. There are mainly two other severity scoring systems, conducted by Mor et al 20 and Pras et al, 21 in addition to Tel Hashomer severity scoring system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Two recent studies also showed that disease severity was not correlated with growth parameters; however, these data were obtained from small numbers of patients. 9,10 Disease severity assessment may be helpful in daily practice in terms of predicting the prognosis and guidance of patients. There are mainly two other severity scoring systems, conducted by Mor et al 20 and Pras et al, 21 in addition to Tel Hashomer severity scoring system.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies including limited numbers of patients addressed the question whether physical growth is affected by genotype and disease severity or not. [5][6][7][8][9][10] However, all these studies utilized an ancient Tel Hashomer severity scoring system, which was not validated in the pediatric population. 11 Thus, in this study, we aimed to analyze the growth parameters in children with FMF according to disease characteristics including genotype and disease severity by a recently validated tool in relatively more patients.…”
mentioning
confidence: 99%
“…recently assessed 51 prepubertal FMF children: the mean height Z‐score significantly increased from −0.64 to −0.26 at 1 year after starting colchicine, compared to the pretreatment period. Importantly, this improvement was substantially absent in those children who had recurrent attacks 50 …”
Section: Pharmacological Treatments For Pediatric Familial Mediterran...mentioning
confidence: 98%
“…Importantly, this improvement was substantially absent in those children who had recurrent attacks. 50 Even though one may expect puberty to be delayed in untreated patients with poor controlled disease, there are no specific studies investigating timing of pubertal onset in patients with FMF; it is therefore not currently possible to evaluate the role of colchicine in potentially improving this issue. 51…”
Section: Colchicine Intolerancementioning
confidence: 99%
“…It is likely that chronic allergic inflammation impairs growth secondarily. Certainly, chronic and recurrent autoinflammation has been shown to negatively impact linear growth, and this impairment can be mitigated with corticosteroid‐sparing immunosuppressive therapy . However, a number of Mendelian disorders have provided additional mechanistic insight into ways in which specific pathway defects that result in atopy may also negatively impact growth.…”
Section: Allergic Disease a Growing Problemmentioning
confidence: 99%